Avaliação de um programa de ensino de habilidades de brincar para crianças com TEA aplicados por mães durante o período de isolamento social - Biazim, Miriana de Araujo (2022)
Autism Spectrum Disorder is a neurodevelopmental disorder characterized by deficits in social communication and restricted interests. Parental training is being a possibility to teach parents about the concepts in Applied Behavior Analysis, expanding the learning opportunities of new behaviors of children. This study aimed to verify whether a procedure for teaching behavioral skills with three mothers would be enough to increase the number of opportunities to play with their daughters with autism and, therefore, increase the number of children's independent responses in games and games. The mothers were taught using three different Teaching Procedures: Video Modeling, Family Guidance and Immediate Feedback. Three dyads were selected, which were included in a Telehealth Program in ABA. The dependent variable measured was the mothers' behavior when playing with their daughters. Playing behavior was operationalized in: selecting the appropriate objects for playing, ensuring the conditions of a favorable environment with a minimum of distractors during the teaching phase, guaranteeing instructional control, that is, the direction and control of mothers through instructions, increase eye contact as a way to increase social engagement and increase shift changes during play proposals. Social engagement in this research was defined as the modification of the mother's facial expression due to the game and the choice of reinforcers. The independent variable was the teaching implemented to teach mothers new behaviors aimed at expanding the repertoire of playing with their daughters. The results achieved their initial objectives and it is possible to observe the expansion of play arrangements between mothers and their daughters through the learning of new behaviors.